Microorganisms of the preorbital glands of the Cape grysbok, Raphicerus Melanotis Thunberg - Ruppel, Annelie,1955- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Agric.)) -- University of Stellenbosch, 1984.